Prispevek k poznavanju metuljev (Lepidoptera) Slovenije - Lesar, Tone (Natura Sloveniae, 2008)
The fauna of Lepidoptera of Slovenia is still poorly known, especially as far as Microlepidoptera are concerned. To encourage regular publishing of new records of rare Lepidoptera species in this region and Slovenia as a whole, the authors consider this contribution as the first in the series. The recordsfrom Stajerska and Koroška include information on 42 Microlepidoptera species new to the region with 5 species recorded in Slovenia for the first time. Records of further 17 Microlepidoptera species with no recent or doubtful records are included. Interesting and significant new records for sixlittle known species of noctuid moths (Noctuidae) in Slovenia are also discussed.
Keywords: Butterflies; Classification; Ecosystem; Ekosistem; Koroška; Lepidoptera; Metulji; Styria; Štajerska